Classical Particle in Presence of Magnetic Field, Hyperbolic Lobachevsky and Spherical Riemann Models - Kudryashov, V.V.; Kurochkin, Yu.A.; Ovsiyuk, E.M.; Red'kov, V.M. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
Motion of a classical particle in 3-dimensional Lobachevsky and Riemann spaces is studied in the presence of an external magnetic field which is analogous to a constant uniform magnetic field in Euclidean space. In both cases three integrals of motions are constructed and equations of motion are solved exactly in the special cylindrical coordinates on the base of the method of separation of variables. In Lobachevsky space there exist trajectories of two types, finite and infinite in radial variable, in Riemann space all motions are finite and periodical. The invariance of the uniform magnetic field in tensor description and gauge invariance of corresponding 4-potential description is demonstrated explicitly. The role of the symmetry is clarified in classification of all possible solutions, based on the geometric symmetry group, SO(3,1) and SO(4) respectively.